Salt Contamination Calculation in Insulators During Monsoon Using Artificial Neural Network - Jewan Singh; Vibhakar Mansotra (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2017)
Control framework consistent quality depends mostly on the natural and climate conditions which cause flashover on contaminated protectors. Such flashover prompts framework blackouts. Close to the beach front zones the salt pollution can be quickly based on the surface of the shields and frame a directing layer by retaining wet from the fog. This layer at times prompts flashover. Investigation of defilement of separator under marine contamination is the point of this examination, and the impacts of different meteorological elements on the disease seriousness have been researched altogether. In the present paper, an endeavour has been made to gauge the contamination severity under different climate conditions amid the stormy season utilising Artificial Neural Organize. The anomaly determination issue has been considered in this work to take out few exceedingly scattered exploratory information. The connection between ESDD with temperature T, stickiness H, weight P, precipitation R and wind speed WV has been created utilising ANN as a function estimator.